Ultrasonographic, histological, cytological and microbiological monitoring Murrah buffalo uterine involution - Ferreira, J. C.P. [UNESP]; Gimenes, L. U. [UNESP]; Rubio, C. [UNESP]; Irikura, C. R. [UNESP]; Wittman, R. M. [UNESP]; Martin, I. [UNESP]; di Santis, G. W.; Oba, E. [UNESP] (My University, 2010)
Aiming monitoring uterine involution in five buffalo from parturition to 50th day of puerperium, daily sonographic examinations were carried out and uterine and cervical diameter, appearance of uterine wall and caruncucles, and uterine contents were recorded. Uterine swabs, cytological and biopsies samples were also taken at postpartum days 2 (D2), D9, D16, D23, D30, D44. The uterine involution of pregnant horn was complete at D35 and the rate of involution was 0.11±0.66. Initially, uterine edema, luminal content, caruncucles and large vessels were seen. From D9 to D16 the edema disappeared and uterine content changed from a coarser hiperecogenic to a more grained and uniform appearance. By D30 the luminal content disappeared. The cervical involution occurred at a rate of 0.13±0.31 cm/day and was completed by D30. The relative PMN neutrophils count in the cytological preparations showed that luminal inflammatory response was initially predominantly moderate or severe turned by D30 to slight or moderate. The mononuclear endometrial infiltration pattern that was initially slight turned to a severe in all animals by D44. The main uterine contaminants were Staphylococcus sp, Streptococcus sp and Arcanobacter sp and all animals but two were free of uterine infections at D44.
Keywords: Buffaloes; Puerperium; Uterine involution